2007
DOI: 10.1111/j.1365-2133.2007.08050.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased lipopolysaccharide-induced tumour necrosis factor-?, interferon-? and interleukin-10 production in atopic dermatitis

Abstract: These results demonstrate that the effects of LPS stimulation depend on both the type of cytokine and the origin of PBMC. Endotoxin exposure is suggested to modulate the disease course of AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 13 publications
1
11
0
1
Order By: Relevance
“…As noted by Niwa [23]; plasma levels of IL-10 seem to correlate inversely with the severity of AD. However, increased production of IL-10 has been demonstrated by other studies [21, 24]. T cells stimulated with IL-12 showed induction of IL-10 in vitro [25].…”
Section: Resultsmentioning
confidence: 90%
“…As noted by Niwa [23]; plasma levels of IL-10 seem to correlate inversely with the severity of AD. However, increased production of IL-10 has been demonstrated by other studies [21, 24]. T cells stimulated with IL-12 showed induction of IL-10 in vitro [25].…”
Section: Resultsmentioning
confidence: 90%
“…We hypothesized that the genetic background, with an important component of African ancestry and a different distribution of susceptibility alleles for eczema could be protective. Also, particular exposures of these children, with early infections as a hallmark, may confer protection, as has been suggested [56,85]. The diagnostic criteria we used [30] are very important when aiming to study this disease in the tropics because infections and other medical conditions producing "itchy skin" are very frequent.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to these findings, other studies have shown either elevated IL-10 levels in PBMC’s isolated from AD patients [148], in lesional skin [149–151], or increased induction of IL-10 in PHA stimulated blood cultures from subjects with AD [152] or PBMC’s [148] and monocytes [151] stimulated with LPS. Elevated numbers of CD4+ and CD8+ cells expressing IL-10 were also observed in patients with AD [79].…”
Section: Th2 Cytokinesmentioning
confidence: 95%